Draft Genome Sequence of Chemolithoautotrophic Acetogenic Butanol-Producing Eubacterium limosum ATCC 8486 - Song, Yoseb (Genome Announc, 2015)
Eubacterium limosum ATCC 8486 is an anaerobic chemolithoautotrophic acetogenic bacterium that converts and transforms syngas and isoflavonoids to butanol and phytoestrogens, respectively. Here, we report the draft genome sequence of the E. limosum ATCC 8486 (4.37 Mb) strain and its annotation information, including syngas fermentation and denitrification metabolic pathways.